Information Skills Course (GXEX1401): A survey of its effectiveness as perceived by students - Chan, Sai Noi; Ramly, Zaharah (University of Malaya Library, 2001)
The Information Skills Programme was formally introduced as a compulsory one-credit university course to all first year students pursuing an undergraduate degree in the University of Malaya in the 1998/1999 academic session. The objective of the Course is to equip students with basic information skills and techniques that will equip them for life-long learning. This report presents the views of some 1000 students on the usefulness of the topics taught in the Course in relation to searching information in the Library and to their learning as well as their assignments. The findings from the survey indicate that students in the first year are more concerned with locating materials prescribed in their reading lists than with searching for additional reference materials from periodical indexes or abstracts, whether printed or electronic. Almost 90% of the students rank OPAC as useful, followed by Search Strategy (85%) and Project Work (79.75%).